Safety and security in the age of synthetic biology - James W. LeDuc; Zhiming Yuan (Journal of Biosafety and Biosecurity, 2019)
Synthetic biology offers great potential for benefit to society, human health and agriculture; however, it also raises new concerns about safety and security. Application of established tools of biosafety and biosecurity along with strong individual and institutional leadership will help alleviate risks, but these may require refinement to address successfully the potential challenges of synthetic biology. Institutional biosafety committees (IBC) are key to providing institutional oversight and as technology evolves, especially in the case of synthetic biology where many different specialized fields may play a role. Membership of the IBC needs to adapt to ensure that sufficient knowledge and experience is available to evaluate projects and recognize potentially dangerous experiments. Recommendations regarding avian influenza gain of function studies may offer a valuable framework of points to consider relevant future studies involving synthetic biology. Keywords: Synthetic biology, Biosafety, Biosecurity, Institutional biosafety committees, Leadership in science